Factors related to perineal outcome after vaginal delivery in primiparas: a cross-sectional study - Marcella Rocha Tavares de Souza; Laryssa Miranda Vidal Cavalcante Farias; Gabriela Lima Ribeiro; Tatiane da Silva Coelho; Camila Chaves da Costa; Ana Kelve de Castro Damasceno (SciELO, 2020)
Abstract Objective: Identify the associations between perineal outcome in primiparas and interventions during labor and delivery, newborn weight and APGAR score. Method: Document-based, correlational, retrospective, quantitative study conducted in a tertiary maternity hospital in the state of Ceará, between July 2017 and January 2018. The independent variables were labor induction, amniotomy, non-pharmaceutical methods for relieving pain, forceps, episiotomy, Kristeller maneuver, position in the expulsion stage, shoulder dystocia, and newborn weight and APGAR score, and the dependent variable was perineal outcome. Pearson's chi-square test and Fisher's exact test were used. Results: A total of 226 normal-risk primiparas who had a vaginal delivery. An association was found between horizontal position in the expulsion stage and episiotomy, and between not performing an episiotomy and perineal tearing. The other variables (labor, delivery and neonatal) did not have any effect on perineal tearing. Conclusion: Interventions, with the exception of episiotomies, did not have an influence on the occurrence of perineal trauma, but they do need to be carefully assessed. Deliveries in a horizontal position were associated with a higher likelihood of performing an episiotomy.